Metamaterial entrenched circular microstrip antenna for Malaysia HAPS - Muhammad Ezanuddin, Abdul Aziz; Mohd Fareq, Malek, Dr.; Soh, Ping Jack; R. Badlishah, Ahmad, Assoc. Prof. Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2010)
Link to publisher’s homepage at http://ieeexplore.ieee.org/